Internalization of Islamic Educational Values for People with Disabilities - Aida Arini; Shobihus Surur; Khoirul Umam; Ainun Fitri Mughiroh; Sholihul Anshori; Burhanuddin Ridlwan; Mochamad Nursalim (Edudeena : Journal of Islamic Religious Education, 2026)
This study examines the process of internalizing Islamic educational values among persons with disabilities within a community-based inclusive educational setting and proposes a conceptual model grounded in empirical findings. While previous studies have predominantly focused on formal institutions, limited attention has been given to how values are internalized in non-formal, community-based environments. This research addresses that gap by analyzing the RUDEKA Community in Jombang, Indonesia. Using a qualitative case study design, data were collected through in-depth interviews, participatory observation, and document analysis. The data were analyzed using the interactive model of Miles, Huberman, and Saldana, supported by triangulation and member checking. The findings reveal that Islamic educational values ṣabr (patience), shukr (gratitude), musyāwarah (deliberation), ta‘āwun (mutual assistance), al-musāwāt (egalitarianism), and al-ukhuwwah al-Islāmiyyah (Islamic brotherhood) are internalized through three interconnected mechanisms: social interaction, spiritual reflection, and creative expression. These mechanisms form an integrative Social-Spiritual-Creative Synergy Model, which contributes to psychological empowerment, spiritual awareness, and inclusive identity formation. This study contributes theoretically by conceptualizing value internalization as a multidimensional experiential process and practically by demonstrating the role of community-based initiatives in inclusive Islamic education.